NURSING INTERVENTIONS TO ENHANCE PATIENT SAFETY IN ACUTE CARE SETTINGS - Amani Mousa Al Qattan, Haya Mohammed Al Salem, Jawaher Mousa Al Qattan, Fetim Sultan Al Harbi, Hakimah Abdulrahim Almuzain, Hussain Yassin Hussain Alalowy,,; Maryam Lafta Jazaa Al-Dhafiri, Abdulaziz Muhammad Mayah Al-Dhafiri, Nada Hussein Mohammad Lasslom, Mohammad Ahmed Saleh Al Sinan, Mashael Khalid Aldossri,Muneerah Abdulrhman Alomar , (Chelonian Research Foundation, 2022)
Introduction: Despite the individual effectiveness of specific nursing interventions, a comprehensive synthesis of the evidence is lacking. The aim of this systematic review is to systematically evaluate and synthesize the existing literature on nursing interventions designed to enhance patient safety in acute care settings. Methods: This systematic review employed a meticulous and comprehensive search strategy across multiple databases, utilizing MeSH terms and keywords to target nursing interventions for patient safety in acute care settings. The systematic study selection process, inclusion/exclusion criteria, rigorous quality mssessment, and transparent data extraction contributed to a reliable and valid synthesis Of evidence, minimizing bias and ensuring a robust review Of nursing interventions' impact on patient safety in acute care. Results: The six randomized clinical trials included in this systematic review displayed significant variation in sample sizes, ranging from 129 to 632 participants. This diversity enabled a comprehensive investigation into the impact of nursing interventions on patient safety across various acute care settings. The trials covered a broad range of clinical settings, including urban tertiary care hospitals, community hospitals, and specialized surgical centers, providing insights into the generalizability ofnursing interventions across diverse healthcare contexts. The evaluated nursing interventions addressed multiple facets of patient safety, such as enhanced medication reconciliation processes, nurse-led communication training programs , increased nursing staff ratios, and a standardized infection prevention protocol. This diversity allowed for a nuanced exploration of the distinct contributions Of various nursing-led approaches to enhancing patient safety in acute care settings. Conclusions: This systematic review highlighted the crucial role of nursing-led interventions in enhancing patient safety within acute care settings, supported by diverse randomized clinical trials demonstrating reductions in medication enors, improved communication, and decreased adverse events and healthcare-associated infections, emphasizing the need for public health decision makers to invest in nursing education, optimal staffing, standardized infection prevention protocols, and interdisciplinary Collaboration to foster a safer patient Care environment. Keywords: Patient Safety, Nursing Interventions, Acute Care, Randomized Clinical Trials, Healthcare Policies.